Organization of marketing activity of coal mining enterprises in an irregular demand environment: theoretic and practical aspects - Zaloznova, Y.; Trushkina, N. (Економічний вісник Донбасу, 2016)
The contents of the term «marketing activity of coal mining enterprise» was revised considering the peculiarities of operation thereof. Factors affecting marketing processes of coal producers were identified. Dynamics of marketing of coal mining companies were analyzed. A forecast of marketing rate of coal mining enterprises were made using various methods of forecasting. A model of contract relationship between coal producer and different categories of customers was developed. Methodological guidelines on improvement of marketing management system of coal mining enterprises were designed. Recommendations on how to arrange marketing networks in the environment of irregular demand for coal were given.